An advanced delay-dependent approach of impulsive genetic regulatory networks besides the distributed delays, parameter uncertainties and time-varying delays - Pandiselvi, Selvakumar; Ramachandran, Raja; Cao, Jinde; Rajchakit, Grienggrai; Seadawy, Aly R. R.; Alsaedi, Ahmed (Nonlinear Analysis: Modelling and Control, 2018)
In this typescript, we concerned the problem of delay-dependent approach of impulsive genetic regulatory networks besides the distributed delays, parameter uncertainties and time-varying delays. An advanced Lyapunov–Krasovskii functional are defined, which is in triple integral form. Combining the Lyapunov–Krasovskii functional with convex combination method and free-weighting matrix approach the stability conditions are derived with the help of linear matrix inequalities (LMIs). Some available software collections are used to solve the conditions. Lastly, two numerical examples and their simulations are conferred to indicate the feasibility of the theoretical concepts.
Keywords: genetic regulatory networks (GRNs); time-varying delays; distributed delays; parameter uncertainty; convex combination method; impulses; linear matrix inequalities (LMIs)